Pengaruh Pelatihan dan Loyalitas Karyawan Terhadap Motivasi Kerja Pada PT Bahtera Dira Adiguna Jakarta Pusat - Ammin, Mochammad; R, Rosento (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This research aims to determine the influence of employee training and loyalty factors on work motivation at PT Bahtera Dira Adiguna, Central Jakarta. This research uses regression analysis, where this analytical tool is used to determine the extent of the influence of training factors and employee loyalty on work motivation. The sampling method used was nonprobability sampling with a saturated sampling technique for 30 employees. The results of this research partially show that the Training variable has a positive and significant effect on work motivation, employee loyalty has a positive and significant effect on work motivation. The research results also show that training and loyalty simultaneously influence work motivation. The research results also prove that the R2 (Coefficient of Determination) value is 0.540, meaning that the work motivation variable (Y) can be explained by training (X1) and employee loyalty (X2) simultaneously at 54.0%.